Optimalisasi Kesadaran Postur Tubuh dan Penggunaan Gadget Sehat dalam Pencegahan Forward Head Posture Anak Sekolah - Raufina Riandhani Mulyoto; Ni Nyoman Melani Karang; A A I Ayesa Febrinia Adyasputri; Hendika Dwinanda Wicaksana (Jurnal Pengabdian Masyarakat (JUDIMAS), 2026)
Forward Head Posture (FHP), also known as "text neck," has become an increasingly prevalent postural issue among school-aged children due to the non-ergonomic use of electronic devices. This condition, characterized by an abnormal forward projection of the head, places chronic stress on the cervical spine, leading to various complaints such as neck pain, headaches, and reduced respiratory function. In response, a community outreach program was implemented to optimize postural awareness and promote healthy gadget usage habits. The intervention employed an educational and participatory methodology, including interactive sessions, demonstrations of correct posture, and hands-on practice of stretching exercises to alleviate muscle tension. The program's success was quantitatively evaluated by comparing pre-test and post-test results to assess the students' level of knowledge and awareness. The findings revealed a significant improvement, with student comprehension scores increasing dramatically following the intervention. While a majority of students initially demonstrated a low understanding of ergonomic principles, a substantial increase in knowledge was observed post-program. This outcome confirms that an educational approach combined with practical application is highly effective in instilling the awareness and skills necessary for FHP prevention, underscoring the importance of early intervention for the musculoskeletal health of the digital generation.